Two new species of Parapharyngodon parasites of Sceloporus pyrocephalus, with a key to the species found in Mexico (Nematoda, Pharyngodonidae) - Garduño Montes de Oca, Edgar Uriel; Mata-López, Rosario; León-Règagnon, Virginia (ZooKeys, 2016)
Two new species of Parapharyngodon collected from the intestine of the Mexican boulder spiny lizard Sceloporus pyrocephalus are described. This study increases to 49 the number of valid species assigned to Parapharyngodon worldwide, 11 of them distributed in Mexico. Males of the two new species share the presence of four pairs of caudal papillae, an anterior echinate cloacal lip and the presence of lateral alae; however, both differ from each other in lateral alae extension and echinate cloacal anterior lip morphology. Females of both species have a prebulbar uterus and eggs shell punctuate with pores, characteristics shared with few other species of Parapharyngodon. Both new species differ from other congeneric species in the papillar arrangement, the anterior cloacal lip morphology, the lateral alae extension and total length/spicule ratio. A taxonomic key for the species of Parapharyngodon distributed in Mexico is provided.